Colorimeter design for dry food-products inspection using TCS3200 sensor and Arduino Mega-2560 - Sulistyo Prabowo; Chandra Kadwa Utama Sutrisno; Krishna Purnawan Candra; Anton Rahmadi; Yuliani Yuliani (Advances in Food Science, Sustainable Agriculture and Agroindustrial Engineering (AFSSAAE), 2023)
This report describes the successful construction of a Colorimeter CK20.1 prototype using a TCS3200 sensor based on the Arduino Mega-2560 microcontroller for solid foodstuffs inspection. The sample color exposed is presented in RGB form. In this experiment, a commercial colorimeter (ColorFlex EZ Spectrophotometer, with the output, is in L*a*b* form) was applied as a validator of the prototype quality performance on color reading for green beans, wheat flour, palm sugar, ground coffee, and cocoa powder. Data were analyzed for mean comparison using t-test or Mann-Whitney for normally or not normally distributed data, respectively. Before data analysis, the RGB data provided by the prototype was transformed to L*a*b* by the template available from colormine.org and vice versa for the data provided by the ColorFlex EZ. The results showed that color component measurement data from the Colorimeter CK20.1 prototype and the Color FlexEZ were significantly different (p<0.05) for all the foodstuffs observed; however, the color produced by each color component is likely very similar visually. Further development of the CK2.1 prototype is being done to provide a cheap and practical color detector.